Deliberation, Southeast Asian Local Wisdom in Resolving Disputes - Rahdiansyah Rahdiansyah; Yulia Nizwana (UIR Press, 2019)
Cultural disputes, and others, often occur between neighboring countries in Southeast Asia and can be the seeds of disharmony, of course, this is not desirable. Southeast Asia as a cultural scope that is interrelated in history, has local wisdom in resolving disputes, resolving this dispute is known as deliberation. Deliberation is an identity that must be prioritized as a wise cultural approach for the ASEAN community. The purpose of this study is to explore the local wisdom of Southeast Asian people in resolving disputes in their communities and implementing them as a solution for the ASEAN community. Recognizing each other as cultural origins often occur between Malaysian and Indonesian communities. As a nation of the same family, this is commonplace, but the most important thing is how to solve it. Interviewing the people of both countries is the first thing to do in looking at this problem, how they understand and see culture in their culture. Questionnaires are distributed as much as possible, each data obtained will be processed and classified according to nationality, education, age, and others. The findings will be a study to see the perspectives of the two countries in understanding history, culture, and cultural results in addressing the differences of opinion that occur. At least the description of the root of the problem is obtained, why this problem occurs, what are the main causes, how to understand it, how to react to it, and lead to the resolution of the dispute over ownership of culture itself